Viable factors to improve the administrative capacity and the execution presupuestal in the Unidad Administrativa Especial de Rahabilitacion y Mantenimiento Vial (UAERMV) (2014)
La Unidad Administrativa Especial de Rehabilitación y Mantenimiento Vial (UAERMV) It is an entity assigned to the Secretariat of Mobility of Bogota. This entity, for his nature of mobility and his importance belong to the sector in the development infraestructural of the city, evidence in the last years a great responsibility opposite to the citizenship as for the improvement of the conditions of the road mesh and the critical current situation of the mobility in the city. Observing this panorama the entity is in the obligation for the force 2014, the execution presupuestal and physical of all the resources that it has to his responsibility both with his internal clients and with the same citizenship there is because of it that arises the following question. How might UAERMV have and improve the administrative aptitude to effect an execution presupuestal of the resources destined for the rehabilitation and road maintenance that has to his post for the force 2014?